2005
DOI: 10.1038/sj.npp.1300959
|View full text |Cite
|
Sign up to set email alerts
|

Big Dynorphin, a Prodynorphin-Derived Peptide Produces NMDA Receptor-Mediated Effects on Memory, Anxiolytic-Like and Locomotor Behavior in Mice

Abstract: Effects of big dynorphin (Big Dyn), a prodynorphin-derived peptide consisting of dynorphin A (Dyn A) and dynorphin B (Dyn B) on memory function, anxiety, and locomotor activity were studied in mice and compared to those of Dyn A and Dyn B. All peptides administered i.c.v. increased step-through latency in the passive avoidance test with the maximum effective doses of 2.5, 0.005, and 0.7 nmol/animal, respectively. Effects of Big Dyn were inhibited by MK 801 (0.1 mg/kg), an NMDA ion-channel blocker whereas those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 55 publications
3
41
0
Order By: Relevance
“…A number of studies reported improved performance in learning and memory tasks after administration of KOR agonists such as U50,488 (Hiramatsu et al, 1996;Hiramatsu and Kameyama, 1998;Hiramatsu and Hoshino, 2004). Likewise, intracerebroventricular administration of Dyn A (1-17) or Dyn B produced dose-dependent increases in stepthrough latency in a passive avoidance test (Kuzmin et al, 2006). However, administration of the prodynorphin-derived peptide BigDynorphin produced increases in step-through latency that were blocked by MK-801 [(ϩ)-5-methyl-10,11-dihydro-5H-dibenzo [a,d] cyclohepten-5,10-imine maleate] instead of nor-BNI, suggesting that this peptide influenced memory through the NMDA receptor (Kuzmin et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies reported improved performance in learning and memory tasks after administration of KOR agonists such as U50,488 (Hiramatsu et al, 1996;Hiramatsu and Kameyama, 1998;Hiramatsu and Hoshino, 2004). Likewise, intracerebroventricular administration of Dyn A (1-17) or Dyn B produced dose-dependent increases in stepthrough latency in a passive avoidance test (Kuzmin et al, 2006). However, administration of the prodynorphin-derived peptide BigDynorphin produced increases in step-through latency that were blocked by MK-801 [(ϩ)-5-methyl-10,11-dihydro-5H-dibenzo [a,d] cyclohepten-5,10-imine maleate] instead of nor-BNI, suggesting that this peptide influenced memory through the NMDA receptor (Kuzmin et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Microinjection of U69593 into the infralimbic cortex reduced anxiety-like behavior in the EPM test [46] . Kuzmin et al (2006) showed that big dynorphin, a prodynorphin-derived precursor peptide, induced anxiolytic-like behavior in mice in the EPM test [47] . Whereas, deletion of the prodynorphin gene increased anxiety-like behaviors in the EPM and light-dark tests [48] .…”
Section: Rodent Models Of Anxietymentioning
confidence: 99%
“…Discrepancies among these studies may be due to, but are not limited to, the use of specific genetic constructs for generating mutant mice, experimental paradigms, size of the apparatus, intensity of illumination, test conditions, animal strains, and lab specific basal stress levels. Although with these limitations and variables, the findings clearly demonstrate that the dynorphin/κ opioid receptor system is involved in anxiety-related behavior [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][49][50][51] (see Table 1 for a summary of current literature), but it is difficult to define the exact role of κ opioid receptor signaling because both anxiolyticand anxiogenic-like effects are reported with κ opioid receptor agonists. Indeed, THC, a CB1 receptor agonist, microinjected at low doses in the prefrontal cortex and ventral hippocampus induced an anxiolytic-like response, while high doses caused an anxiogenic reaction [52] .…”
Section: Rodent Models Of Anxietymentioning
confidence: 99%
“…These effects are hypothesized to be mediated by modulating neuronal firing, and the release of neurotransmitters and hormones (21,22). Dynorphins, for example dynorphin A (Dyn A), Dyn B and α-neoendorphin, are derived from the long precursor prodynorphin (Pdyn), and modulate cognition through κ-opioid receptors (KOR) (23)(24)(25). Enkephalins, namely met-and leu-enkephalins, are produced by the proteolytic cleavage of pre-proenkephalin (Penk), which is responsible for the modulation of learning and memory (26), synaptic plasticity (27), and emotional behaviors (28).…”
Section: Introductionmentioning
confidence: 99%